Na+ diffusion kinetics in nanoporous metal-hexacyanoferrates. Issue 2 (29th September 2015) - Takachi, Masamitsu; Fukuzumi, Yuya; Moritomo, Yutaka
Abstract : Metal-hexacyanoferrates (metal-HCFs) are promising candidates for cathode materials of sodium-ion secondary batteries (SIBs). Abstract : Metal-hexacyanoferrates (metal-HCFs) are promising candidates for cathode materials of sodium-ion secondary batteries (SIBs). Here, we systematically investigated Na + diffusion constants ( D ) and the activation energies ( E a ) of metal-HCFs against the framework size (= a /2). We found that the magnitude of D ( E a ) systematically increases (decreases) with increases in a, indicating that steric hindrance plays a dominant role in Na + diffusion.